PRIMARY GRADE STUDENTS IN THE PROCESS OF TEACHING MATHEMATICS PROBLEMS (BOSHLANG`ICH SINF O`QUVCHILARIGA MATEMATIKA O`QITISH JARAYONIDA MUAMMOLAR) (Conferencea, 2023)
Today, based on competence approach in the conditions of education, the teachers approach their work why you should also change. From now on, the teacher will not be birgir of "objective knowledge" together with the textbook to the students.